2017
DOI: 10.2147/nsa.s131412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of barium-coated halloysite nanotube addition on the cytocompatibility, mechanical and contrast properties of poly(methyl methacrylate) cement

Abstract: Halloysite nanotubes (HNTs) were investigated as a platform for tunable nanoparticle composition and enhanced opacity in poly(methyl methacrylate) (PMMA) bone cement. Halloysite has been widely used to increase the mechanical properties of various polymer matrices, in stark contrast to other fillers such as barium sulfate that provide opacity but also decrease mechanical strength. The present work describes a dry deposition method for successively fabricating barium sulfate nanoparticles onto the exterior surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…137 HNTs coated with barium were embedded into poly (methyl methacrylate) (PMMA) bone cement, which enhanced the strength and radio-impermeability, improving image quality. 138 In addition, the equilibrium swelling ratio, porosity, and pore size of polyacrylamide (PAAm)/PVA-based hydrogels supplemented with HNTs were decreased, which reduced medium penetration and slowed down the degradation process. 139 By adding thiolated HNTs, the mechanical strength and cross-linking density of the hydrogel were increased, and the swelling rate was reduced.…”
Section: Gastrointestinal Disease Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…137 HNTs coated with barium were embedded into poly (methyl methacrylate) (PMMA) bone cement, which enhanced the strength and radio-impermeability, improving image quality. 138 In addition, the equilibrium swelling ratio, porosity, and pore size of polyacrylamide (PAAm)/PVA-based hydrogels supplemented with HNTs were decreased, which reduced medium penetration and slowed down the degradation process. 139 By adding thiolated HNTs, the mechanical strength and cross-linking density of the hydrogel were increased, and the swelling rate was reduced.…”
Section: Gastrointestinal Disease Treatmentmentioning
confidence: 99%
“…The addition of HNTs to methacrylic gelatin hydrogel enhanced mechanical properties and promoted bone regeneration in rat skull defect models (Figure b) . HNTs coated with barium were embedded into poly (methyl methacrylate) (PMMA) bone cement, which enhanced the strength and radio-impermeability, improving image quality . In addition, the equilibrium swelling ratio, porosity, and pore size of polyacrylamide (PAAm)/PVA-based hydrogels supplemented with HNTs were decreased, which reduced medium penetration and slowed down the degradation process .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Generating and storing electricity has tremendous impact on technological advancements and human civilization. Henry Moissan demonstrated the potential use of electrolysis in industry and science when he isolated fluorine [25]. The phenomenon of electrolysis was a crucial chemical method that helped shape chemistry and manufacturing.…”
Section: Electrodeposition For Metallizing Hntsmentioning
confidence: 99%
“…HNTs, which acted both as the resin bulk and as a nanocarrier for antibiotics also sustained the release of barium sulphate (radiopaque agent). [161][162][163] In other examples the incorporation of HNTs into bioscaffolds made of chitosan, agarose and gelatin enhanced scaffold strength, and adhesion to cells. In vivo studies in rats showed neoangiogenesis at the scaffold proximity without any inflammatory reactions.…”
Section: Bioscaffolds and Tissue Engineeringmentioning
confidence: 99%